Aminated mesoporous silica nanoparticles for the removal of low-concentration malodorous aldehyde gases. Issue 11 (10th October 2018) - Peng, Shengpan; Deng, Yuzhou; Li, Weiman; Chen, Jiayuan; Liu, Haidi; Chen, Yunfa
Abstract : A new strategy of preparing functionalized mesoporous silica nanoparticles without sacrificing their surface area for the effective removal of low-concentration malodorous aldehyde gases. Abstract : Malodorous aldehyde gases, such as n -butyraldehyde, are not only problematic volatile organic compound pollutants but also have offensive odors with a very low olfactory threshold (ppb), which can reduce the quality of daily life even at a very low concentration (0.1–10 ppm). Materials such as activated carbon (AC), metal–organic frameworks (MOFs), and mesoporous silica nanoparticles (MSNs) represent prime candidates for air quality remediation owing to their overall high surface area and accessibility of surface functionalization. Flammability and Chinese government policies on the use of AC and the high cost of MOFs discourage their development and application. MSNs have been the focus of substantial research recently owing to their high specific surface area and pore volume, and surface-modifiable chemical properties because of Si–OH groups. However, pore clogging, due to the high load of functional groups, limits improvement of the MSNs' adsorption performance. Also, the processes of functionalization are complex and time-consuming. Here, we used a new strategy to synthesize ordered mesoporous silica with a high specific area (1000 m 2 g −1 ) and adsorption capability (62.92 mg n -C4 H8 O per g of adsorbent), as well as high loading of amino groups, without pore filling from a one-step sol–gel process at room temperature. The high adsorption capacity on the amine surface in this study reveals the potential utility of MSNs as malodorous aldehyde gas abatement materials.